Law of probability distribution of displacements tables of random substitution linear approximations - Лисицкий, К.Е. (Radiotekhnika, 2017)
We give a refined proof of the law of distribution of the probabilities of bias of tables of linear approximations of random permutations, and also the admissibility of the approximation of this law by the normal law of probability distribution.